ISLAM AND LEGISLATION IN LAW NUMBER 17 OF 2023 ABOUT HEALTH - Razi Purnama, Fachrur (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2024)
The Health Law is a law that regulates various aspects of health in Indonesia, this law was passed by the DPR through a plenary session on July 11, 2023, Law number 17 of 2023 concerning health is a refinement of the previous Health Law, namely Law Number 36 of 2009 concerning Health. However, after the enactment of this law, there were several points of the formation procedure and substance of the law that resulted in polemics in the community, such as the elimination of mandatory spending, the lack of public participation in the formation process and the lack of transparency of legislators in the process of forming this law. This research is a type of library research, and this research is normative legal research. The results of this study are that in the perspective of legal science there are still formal defects in the formation of Law No. 17 of 2023 concerning health where in the formation process it does not provide ample space for the community to provide its aspirations, so that when Law No. 17 of 2023 is enacted it causes a lot of rejection and criticism in the community because it is feared that it will have an impact on health workers and also have an impact on community life. This is reinforced by the theory of sulthah tasyrī'iyah where the process of forming laws and regulations must be based on the welfare of the ummah as a fiqh rule which states that every policy issued by a leader must prioritize maslahat and avoid ugliness.